Consensus Terminology for Point of Care Ultrasound Studies with Incomplete Documentation and Workflow Elements - Jason Nomura; Matthew Flannigan; Rachel Liu; Daniel Theodoro (CINQUILL Medical Publishers Inc., 2022)
Point of Care Ultrasound (POCUS) use by emergency physicians has grown in both breadth and depth of clinical use [1-3]. POCUS workflow is different from a traditional imaging-based specialist workflow because a single clinician orders, obtains images, interprets, and reports the exam results. Traditionally, multiple individuals participate in the workflow: the clinician places the order; an ultrasound technologist reconciles order and identifiers and acquires images; lastly an imaging specialist interprets the exam and creates a report.  hese contrasting approaches has led to unique challenges in streamlining POCUS workflows and identifying disruptions, errors and potential corrections given the differences from radiology focused workflow and resources.